2004
DOI: 10.1038/sj.ejcn.1601859
|View full text |Cite
|
Sign up to set email alerts
|

Rapid carbohydrate digestion rate produced lesser short-term satiety in obese preschool children

Abstract: Objective: To examine whether high carbohydrate meals with different carbohydrate digestion rates have an effect on the short-term satiety in normal and obese preschool children. Subjects and setting: In total, 48 children of both gender, 24 normal and 24 obese, according to body mass index, aged between 3 and 6 y, were selected from children who were attending to a day-care center where they consumed three meals in the day. Interventions: Rapid (potato-based meal) and lente (spaghetti-based meal) carbohydrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 36 publications
(33 reference statements)
1
21
0
1
Order By: Relevance
“…A study investigating the effects of dietary GI and glycaemic load on energy metabolism and voluntary food intake in obese children showed that high-GI meals elicit a sequence of hormonal changes that might limit the availability of metabolic fuels and cause overeating in children (Ludwig et al, 1999). An increase in postpandial satiety by consuming lower dietary GI has been reported in some related studies (Ball et al, 2003;Warren et al, 2003;Alvina and Araya, 2004), while another study reported an inverse relationship between appetite and postprandial blood glucose response (Anderson et al, 2002).…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…A study investigating the effects of dietary GI and glycaemic load on energy metabolism and voluntary food intake in obese children showed that high-GI meals elicit a sequence of hormonal changes that might limit the availability of metabolic fuels and cause overeating in children (Ludwig et al, 1999). An increase in postpandial satiety by consuming lower dietary GI has been reported in some related studies (Ball et al, 2003;Warren et al, 2003;Alvina and Araya, 2004), while another study reported an inverse relationship between appetite and postprandial blood glucose response (Anderson et al, 2002).…”
Section: Introductionmentioning
confidence: 70%
“…A crossover study has reported a lower lunch intake in a group of young children who consumed low-GI breakfast compared with those after high-GI breakfast (Warren et al, 2003). Ball et al (2003) demonstrated a prolongation of satiety following an intervention with a low-GI meal replacement, while Alvina and Araya (2004) observed significantly less satiety in obese children after consumption of a carbohydrate meal with a rapid digestion rate. Although some studies did not suggest an increase postprandial satiety by increasing dietary GI (Heini et al, 1998;Anderson et al, 2002), providing snacks with lower GI values probably cause no harm and possibly reduce the frequency of snacking due to hunger.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to sweets' intake, recent results in similar children in Chile would suggest that a significant lesser satiety is observed after consumption of a high carbohydrate meal with a rapid digestion rate, indicating a decreased capacity of energy regulation in obese children (Alvina and Araya, 2004). It has also been suggested that a higher sugar intake decreases intake of fruit and beverages and was positively associated with BMI in 4-yearold Norwegian boys (Overby et al, 2004).…”
Section: Discussionmentioning
confidence: 90%
“…In elderly subjects, mashed potatoes (high-GI food) induced significantly higher glycaemia and satiety compared with a barley meal (low-GI food) containing the same amount of available carbohydrates as measured during 120 min (Kaplan and Greenwood, 2002). In contrast, a lower satiety was observed in obese children after consumption of a rapidly digested carbohydrate meal (including potatoes) compared with a lente meal (including spaghetti; Alvina and Araya, 2004). In the latter study, no difference was found in normal weight children.…”
Section: Introductionmentioning
confidence: 93%